Efficacy of Cardiac Blood Pool Activity in Hepatobiliary Scintigraphy for Diagnosis of Neonatal Hepatitis in Patients with Suspected Biliary Atresia (Bangladesh Journal of Nuclear Medicine, 2018)
Background: Biliary atresia (BA) is the commonest fatal liver disorder in children. It results from developmental anomaly due to fibrosis of extra hepatic bile ducts. The reported global incidence of biliary atresia varies from 5/100,000 to 32/100,000 live births. Accurate diagnosis is important before 8 weeks of age, since hepatoportoenterostomy (Kasai’s procedure) has a 90% success rate at this stage whereas success rate drops to 20% beyond 3 months. On the other hand, neonatal hepatitis (NH) which is other most common cause of neonatal cholestasis (NC) needs conservative treatment. So, differentiation of biliary atresia from neonatal hepatitis is very crucial. Hepatobiliary scintigraphy (HBSG) is most popular method to differentiate biliary atresia from neonatal hepatitis. But in severe neonatal hepatitis the diagnosis become inconclusive when excretion of radiotracer in bowel become absent along with prolonged cardiac activity. Prolonged cardiac blood pool activity in hepatobiliary scintigraphy is an indication of hepatocyte destruction in neonatal hepatitis. The aim of the study was to assess the efficacy of cardiac blood pool in hepatobiliary scintigraphy for diagnosis of neonatal hepatitis in suspected biliary atresia patient.Patients and methods:  A total of 24 infants with history of conjugated hyperbilirubinaemia underwent HBSG showed prompt cardiac blood pool activity (9 infants) and also with prolonged cardiac blood pool (15 infants) with no excretion of radiotracer in bowel either in early or delayed images was included in the study. The findings of HBSG were compared with percutaneous liver biopsy findings and analyzed.Result: Among 24 infants prolonged cardiac blood pool activity in HBSG was observed in 11 (73.3%) BA infants and 4 (44.4%) of NH infants. Absent bowel activity with prompt clearance of cardiac blood pool activity was observed in 4 (26.7%) BA infants and 5 (55.6%) NH infants. The difference was not statistically significant (p>0.05).The calculated sensitivity of cardiac blood pool activity in HBSG for evaluation of NH was 44.4%, specificity was 26.7%, accuracy was 33.3%, positive predictive value (PPV) was 26.7% and negative predictive value (NPV) was 44.4%. The sensitivity, specificity, PPV, NPV and accuracy were low due to large number of false positive infants which might be due to complete obstruction of bile duct or due to early hepatocyte destruction (within 3 months of age).Conclusion: Although prolonged cardiac blood pool activity was considered as diagnostic criteria for the diagnosis of NH in suspected BA patient but it could not be able to differentiate these two conditions.Bangladesh J. Nuclear Med. 20(2): 124-128, July 2017